2021
DOI: 10.3390/solids2010001
|View full text |Cite
|
Sign up to set email alerts
|

Composition, Thermal Expansion and Phase Transitions in Framework Silicates: Revisitation and Review of Natural and Synthetic Analogues of Nepheline-, Feldspar- and Leucite-Mineral Groups

Abstract: Framework silicates form about 70% of the Earth’s crust, mainly feldspars ~50–60% and quartz ~10–15%. Less-abundant feldspathoids include nepheline-, leucite-, and sodalite-group minerals, rich in structurally challenging properties. This review paper deals with anhydrous feldspar-, nepheline-, and leucite/pollucite groups, emphasising the importance of parallel studies on natural and synthetic samples. Four topics are covered. For decades, petrologists have analysed nephelines and recalculated their compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 114 publications
1
14
0
Order By: Relevance
“…The XRD diagrams (Figure 1) were similar for all solids (i.e., the signals had the same angle). However, the XRD patterns for the Ph-HCl material showed more intense signals related to the feldspar group minerals (sanidine, analcime, and nepheline) [19]. In the case of the materials containing Ni, no clear evidence of NiO crystal phase was found.…”
Section: Catalysts Characterizationmentioning
confidence: 85%
“…The XRD diagrams (Figure 1) were similar for all solids (i.e., the signals had the same angle). However, the XRD patterns for the Ph-HCl material showed more intense signals related to the feldspar group minerals (sanidine, analcime, and nepheline) [19]. In the case of the materials containing Ni, no clear evidence of NiO crystal phase was found.…”
Section: Catalysts Characterizationmentioning
confidence: 85%
“…Note that the cell parameter ‘strains’ calculated will reflect errors involved in the estimation of x 0 values with the largest errors occurring at the temperatures furthest from the phase transition. The a 0 , b 0 , c 0 and V 0 values for KMg-Lc were obtained in a similar way from the parameters reported in Table 1 (Redfern and Henderson, 1996); Henderson (2021) has already made a preliminary study of the spontaneous strains for the KMg-Lc data in a review of composition, thermal expansion and phase transitions in framework silicates.
Fig.
…”
Section: Experimental Methodsmentioning
confidence: 87%
“…We have already predicted that P 2 1 / c KZn-Lc should show a phase transition to Pbca at ~700 K (Bell and Henderson, 2018), but the high-temperature data for KZn-Lc reported here show the phase transition occurring over the temperature range 848–863 K where both monoclinic and orthorhombic phases are present. This two phase region is similar to that described for unquenchable, displacive phase transitions shown by kalsilite analogues in the SrAl 2 O 4 –BaAl 2 O 4 system and was named the ‘region of coexistence’ (Henderson and Taylor, 1982); based on similarities shown for displacive phase transitions occurring in ZrO 2 and high-cristobalite, it was suggested that the aluminate ‘nepheline/kalsilite-type’ phase transition had properties of a strain-related martensitic transition (Henderson and Taylor, 1982; Avdeev et al , 2007; Henderson, 2021).…”
Section: Powder Xrd Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, these particles had a chemistry similar to that of leucite, which could testify the reaction of feldspar with the alkaline elements from the organic substance [73]. Therefore, this reaction could probably favor the combustion processes of silica-undersaturated phases [74], which are not present in the natural sediments of the Po Valley.…”
Section: Discussionmentioning
confidence: 99%